2022
DOI: 10.3390/app12168121
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Literature Review of Relative Fundamental Frequency (RFF) in Individuals with and without Voice Disorders

Abstract: Relative fundamental frequency (RFF) is an acoustic measure that characterizes changes in voice fundamental frequency during voicing transitions. Despite showing promise as an indicator of vocal disorder and laryngeal muscle tension, the clinical adoption of RFF remains challenging, partly due to a lack of research integration. As such, this review sought to provide summative information and highlight next steps for the clinical implementation of RFF. A systematic literature search was completed across 5 datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In the same scoping review [21], the results obtained for offset cycle 10 in patients with vocal disorders were lower than those in healthy individuals. The RFF has been studied in patients with spasmodic dysphonia [29], Parkinson's disease [18], and VH with and without phonotraumatic lesions [2,17,28].…”
Section: Mtd Groupmentioning
confidence: 89%
See 3 more Smart Citations
“…In the same scoping review [21], the results obtained for offset cycle 10 in patients with vocal disorders were lower than those in healthy individuals. The RFF has been studied in patients with spasmodic dysphonia [29], Parkinson's disease [18], and VH with and without phonotraumatic lesions [2,17,28].…”
Section: Mtd Groupmentioning
confidence: 89%
“…Roy et al [28] found values between 2 and 3 ST for onset cycle 1 in controls from their sample, which they compared with patients with MTD. In the scoping review mentioned previously, they concluded that onset cycle 1 values ranged from 1.68 to 3.82 ST, with a median value of 2.60 ST [21].…”
Section: Healthy Voicesmentioning
confidence: 96%
See 2 more Smart Citations
“…A series of voice analysis tools includes many components to evaluate speech functions and voice quality [1,2]. The quantitative evaluation of voice quality using acoustics is advocated [3], and two metrics in this sector are the Acoustic Voice Quality Index (AVQI) and the Acoustic Breathiness Index (ABI) [4].…”
Section: Introductionmentioning
confidence: 99%